2008
DOI: 10.2174/156652408786733720
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae and Caveolins in the Respiratory System

Abstract: Caveolae are flask-shaped invaginations of the plasma membrane that are present in most structural cells. They owe their characteristic Omega-shape to complexes of unique proteins, the caveolins, which indirectly tether cholesterol and sphingolipid-enriched membrane microdomains to the cytoskeleton. Caveolins possess a unique scaffolding domain that anchors receptors, ion channels, second messenger producing enzymes, and effector kinases, thereby sequestering them to caveolae, and modulating cellular signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 117 publications
(189 reference statements)
1
57
0
Order By: Relevance
“…In this regard, it appears that caveolae may differentially modulate ASM responses to cytokines such as TNF-␣ vs. IL-13, at least in part due to caveolar vs. noncaveolar expression of their respective receptors (265). In contrast to these [Ca 2ϩ ] i /contraction data, reduced caveolin-1 expression has been reported to facilitate ASM proliferation (89,91,93). Thus it could be reasoned that caveolin-1 contributes to the balance between contractile vs. proliferative phenotype of ASM in the context of inflammation but in either fashion enhance airway changes in asthma for example.…”
Section: L918mentioning
confidence: 95%
See 1 more Smart Citation
“…In this regard, it appears that caveolae may differentially modulate ASM responses to cytokines such as TNF-␣ vs. IL-13, at least in part due to caveolar vs. noncaveolar expression of their respective receptors (265). In contrast to these [Ca 2ϩ ] i /contraction data, reduced caveolin-1 expression has been reported to facilitate ASM proliferation (89,91,93). Thus it could be reasoned that caveolin-1 contributes to the balance between contractile vs. proliferative phenotype of ASM in the context of inflammation but in either fashion enhance airway changes in asthma for example.…”
Section: L918mentioning
confidence: 95%
“…Furthermore, signaling mechanisms within ASM itself could be involved. For example, caveolin-1 can inhibit proliferation (7,89,92), whereas the SOCE mechanisms STIM1 and Orai1 can enhance TGF-␤1-induced proliferation (79) (Fig. 5).…”
Section: L921mentioning
confidence: 99%
“…caveolae; lung; inflammation; cytokine; MAP kinase; RhoA; small interfering RNA CAVEOLAE, FLASK-SHAPED PLASMA membrane invaginations rich in cholesterol and sphingolipids, express any of three caveolin proteins (caveolin-1, caveolin-2, and/or caveolin-3). By virtue of caveolar expression of agonist receptors, ion channels, and other membrane proteins, as well as the association of caveolins with intracellular proteins, the role of caveolins as organizers and facilitators of signal transduction is now well recognized (12,23,38,62,67,81,82).Multiple studies including our own (16,28,33,61,68,73), have now demonstrated the presence of caveolae and caveolins in airway smooth muscle (ASM …”
mentioning
confidence: 99%
“…Multiple studies including our own (16,28,33,61,68,73), have now demonstrated the presence of caveolae and caveolins in airway smooth muscle (ASM …”
mentioning
confidence: 99%
“…Cav-1 regulates the contractile phenotype of maturing airway smooth muscle cells under influence of TGF-␤1 (15). Altered expression of Cav-1 has been implicated in the pathogenesis of several lung diseases (14). Cav Ϫ/Ϫ mice have thickened alveolar walls and irregular alveolar spaces with increased deposition of extracellular matrix and TGF-␤ activity, whereas overexpression of Cav-1 aggravates lipopolysaccharide (LPS)-induced inflammation and subsequent lung injury (17,29).…”
mentioning
confidence: 99%